A singularidade florística dos campos rupestres sensu stricto no município de Itutinga, MG - Arruda, Iago Augusto de Castro (2017)
The advance of science connected to the study of plant diversity has occurred slowly, reaching its maximum only from XIX century. In colonial countries as Brazil, the study of plant diversity was developed under an exploratory point of view, leaving gaps about Brazilian diversity knowledge. Considering the growing concern to understand biological diversity, the Global Strategy for Plant Conservation and the Global Taxonomy Initiative has encouraged the accomplishment of floristic inventories. Within that perspective, the Rupestrian Grasslands constitute a peculiar mountain ecosystem characterized by great edaphic and climatic variations, and the remarkable presence of rock outcrops. These regions show high species diversity and endemism distributed in disconnected formations. Despite this, many sites along Campo das Vertentes (MG) still are poorly known about its floristic composition. Therefore, this research intends to assist in the comprehension of species richness and distribution in the Campo das Vertentes‟ (MG) mountains. To achieve that goal, we developed a floristic inventory restricted to angiosperms on Rupestrian Grassland sensu stricto vegetation; a descriptive characterization of the vegetation; and a floristic similarity analysis between three mountains known as “Serra do Ouro Grosso”, “Serra da Chapada” and “Pombeiro/Galinheiro” formation. All these mountains are located in Itutinga (MG). The inventory considered the data available at herbarium virtual collections, ESAL herbarium collection, and expeditions surveys to collect botanic material. The expeditions occurred in two moments, the first was from March 2010 to February 2012 and the second from July 2015 to July 2016. A total of 365 species and 33 morphospecies was registered. The richest families was Asteraceae (62 spp.), Poaceae (35 spp.), Melastomataceae (23 spp.), Cyperaceae (20 spp.) and Fabaceae (16 spp.). The vegetation revealed a great influence of Cerrado domain and a singular floristic diversity for each mountain studied. The presence of endemics species threatened of extinction at this vegetation is under high degree of anthropogenic threat and demands for urgent conservation policies for the "Campo das Vertentes‟ mountains.